PRODUKSI DAN JUMLAH JENIS IKAN YANG TERTANGKAP OLEH NELAYAN DI SUNGAI KAHAYAN KECAMATAN PAHANDUT KOTA PALANGKARAYA PROVINSI KALIMANTAN TENGAH - Sweking Sweking; Idiannor Mahyudin; Emmy Sri Mahreda; Umi Salawati (Universitas Lambung Mangkurat, 2011)
The purpose of the research is to analyze fish production that the fishermen got from kahayan river, during 10 years (1998-2007), also to inventory kinds of fish that could be catch during 10 year, and the fishermen’s income from it. The research is concluded that fish production is always on decrease : in 1998 the sum of production is 5.272 kg / soak and in 2007 it was 1.840 kg/ soak. During 10 years fish production happened on decrease which was 3.432 kg / soak or 9.52 % from the sum of production completely which was 36.021 kg/soak. There were 29 kinds of fish that consists of 23 genus , 17 species and 6 ordo some of kinds of rare fish that were Botia/ Tangkari (Chormobotia maerants), Tembubuk (Nandus nebulusus) and Arwana / Tangkalasa ( Sekleropagus fomosus). The fishermen’s income during 5 years ago in year 2003 until 2007 was about between Rp. 15.000.000; - Rp 19.000.000; . The decrease of production is followed by fishermen’s income.